Effect of quercetin on the transport of ritonavir to the central nervous system in vitro and in vivo - Liang Gongwen; Li Na; Ma Liping; Qian Zhonglian; Sun Yuwen; Shi Luwen; Zhao Libo (Acta Pharmaceutica)
The aim of this study was to identify an effective flavonoid that could improve the intracellular accumulation of ritonavir in human brain-microvascular endothelial cells (HBMECs). An in vivo experiment on Sprague-Dawley rats was then designed to further determine the flavonoid’s impact on the pharmacokinetics and tissue distribution of ritonavir. In the accumulation assay, the intracellular leve l of ritonavir was increased in the presence of 25 mmol L−1 of flavonoids in HBMECs. Quercetin showed the strongest effect by improving the intracellular accumulation of ritonavir by 76.9 %. In the pharmacokinetic study, the presence of quercetin in the co-administration group and in the pretreatment group significantly decreased the area under the plasma concentration-time curve (AUC0–t) of ritonavir by 42.2 % (p < 0.05) and 53.5 % (p < 0.01), and decreased the peak plasma concentration (cmax) of ritonavir by 23.1 % (p < 0.05) and 45.8 % (p < 0.01), respectively, compared to the control group (ritonavir alone). In the tissue distribution study, the ritonavir concentration in the brain was significantly increased 2-fold (p < 0.01), during the absorption phase (1 h) and was still significantly higher (p < 0.05) during the distribution phase (6 h) in the presence of quercetin.